2020
DOI: 10.1177/1066480720933537
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of School-Based Family Counseling on Elementary Students and Their Families

Abstract: A family counseling intervention grounded in systemic family therapy was conducted in a Title I school-based setting with ( N = 48) kindergarten through sixth-grade student-clients and their primary caregivers. Families’ perception of family communication and satisfaction on the Family Adaptability and Cohesion Evaluation Scale-IV was investigated to determine changes in the percentile score at three benchmarks. A repeated measure analysis of variance indicated a statistically significant difference over time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…As in Carr's (2018), study, family counseling is one of the alternative steps that are systematic as a support to the process of individuals and family members changing to achieve the goal of well-being in family life. Kelchner et al (2020), also provided an example of the school's success in improving academic performance and building the character of students when the school implements family counseling in the school setting. Family counseling that is able to affect the internal changes of a family system is definitely able to give a consistent reaction to changes in behavior, environment and overall sub-system action choices in the family system (Johnson & Ray, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in Carr's (2018), study, family counseling is one of the alternative steps that are systematic as a support to the process of individuals and family members changing to achieve the goal of well-being in family life. Kelchner et al (2020), also provided an example of the school's success in improving academic performance and building the character of students when the school implements family counseling in the school setting. Family counseling that is able to affect the internal changes of a family system is definitely able to give a consistent reaction to changes in behavior, environment and overall sub-system action choices in the family system (Johnson & Ray, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…So basic needs such as love, family acceptance and attention to their development are ignored and not met properly are among the factors that drag these children at risk of being involved in various social problems early in their lives (Nisa, 2021). Kelchner (2020) found that children with disturbed mental and emotional well-being tend to face disciplinary issues at school, are subjected to disciplinary actions such as suspension from school and punishment for various behavioral problems and have a high frequency of skipping school.…”
Section: Introductionmentioning
confidence: 99%